A multinuclear magnetic resonance spectroscopy study of E/Z configurational isomers of unsymmetrical N-alkyl-N-alkyl(aryl)-N'-acylthioureas of platinum(II) complexes - Mtongana, Sibusiso (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD)--University of Stellenbosch, 2006.